The cumulative and residual fatigue response associated with soccer-specific activity performed on different playing surfaces - Page, R. M.; Langley, B.; Finlay, M. J.; Greig, M.; Brogden, C. (Journal of Sports Sciences, 2020)
This study aimed to assess the effect of playing surface (Natural [NT] and Artificial [AT] Turf) on the fatigue response to a soccer-specific exercise protocol (SSEP). Eighteen male soccer players completed the SSEP on NT and AT with pre-, post-, and 48 h post-assessments of eccentric knee flexor (eccKF) and concentric knee extensor peak torque (PT), peak countermovement (CMJ) and squat jump (SJ) height, and Nordic hamstring break angle. No significant main effects for surface or any surface and time interactions were observed for any of the outcome measures, except for eccKF PT recorded at 3.14 rad/s, which was significantly lower 48 h post-trial in the AT condition (AT = 146.3 ± 20.4 Nm; NT = 158.8 ± 24.7 Nm). Main effects for time were observed between pre- and post-trial measures for eccKF PT at all angular velocities, Nordic break angle, CMJ and SJ height. Nordic break angle, and both CMJ and SJ height were significantly impaired 48 h post-trial when compared to pre-trial. The findings of the current study suggest surface dependent changes in eccKF PT which may have implications for recovery and subsequent performance after competition on AT. KEYWORDS: Football, artificial, natural, peak torque, isokinetics, jump height